BIOMETRIC ANALYSIS OF THE ARTIFICIAL HYBRIDIZATION BETWEEN Pangasius djambal BLEEKER, 1846 AND Pangasianodon hypophthalmus SAUVAGE, 1878 - Gustiano, Rudhy (Indonesian Journal of Agricultural Science, 2004)
It is really important, since the possible use of these pangasiid hybrids in aquaculture faces the problem of potential impact on wild population. Therefore, it is urgently needed to provide quick identification tools in the field. This study investigated morphological characters of Pangasius djambal and Pangasianodon hypophthalmus and their hybrids. A detailed morphological analysis using 32 morphometric measurements and five meristic counts was done on the hybridization of P. djambal and P. hypophthalmus. Morphometric analysis and meristic counts showed that the reciprocal hybrids have intermediate characters except for gill raker number in which lower than that of parental species. In general, the hybrids have tendency to be like P. hypophthalmus rather than P. djambal. The only typical character of P. djambal appeared on hybrids is teeth shape, both vomerine and palatine. It is clearly defined that the true hybrids have seven pelvic fin rays.